The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3906/sag-2106-28
|View full text |Cite
|
Sign up to set email alerts
|

Nonscarring scalp alopecia: Which laboratory analysis should we perform on whom?

Abstract: Background/aim: Vitamins and minerals are thought to play an essential but not entirely clear role in developing, preventing, and treating nonscarring alopecia. Telogen effluvium, androgenetic alopecia, and alopecia areata are the most common forms of nonscarring alopecias. We would like to present a different perspective on laboratory abnormalities in patients with nonscarring alopecia. Materials and methods:A total of 467 patients (287 females, 180 males) were included retrospectively. 160 patients in the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…The role of vitamin B 12 in the hair growth cycle has been suggested by various authors [28,29,34]. Tamer et al did not observe any differences in the serum concentration of vitamin B 12 between their group of patients with diffuse hair loss (study group) and healthy controls, which is consistent with our observations.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The role of vitamin B 12 in the hair growth cycle has been suggested by various authors [28,29,34]. Tamer et al did not observe any differences in the serum concentration of vitamin B 12 between their group of patients with diffuse hair loss (study group) and healthy controls, which is consistent with our observations.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, some authors have investigated and reported an association between ferritin deficiency and hair loss [34,35]. Öner et al observed low serum ferritin, the storage form of iron, in patients with non-cicatricial alopecia, especially among women.…”
Section: Discussionmentioning
confidence: 99%